Evaluation of Students’ Communicative Language Ability and Difference Analysis in an Interactive Teaching Environment - Zhao, Xin; Song, Jiao; Wang, Ru; Jiao, Fengming; Gao, Mingli (International Journal of Emerging Technologies in Learning (iJET), 2023)
As the demand for cross-cultural communication has been increasing because of globalization, communicative language ability (CLA) has become an important component of quality education for college students. CLA evaluation and difference analysis help educators understand and identify problems and shortcomings of students in the learning process. However, most of the existing CLA evaluation and difference analysis methods focus on written and oral tests of college students in an interactive teaching environment, instead of evaluating actual communicative ability in the interactive environment. Therefore, this research aimed to study the CLA evaluation of college students and difference analysis in an interactive teaching environment. The environment for improving the CLA was analyzed first. After setting up five-level evaluation indexes for the CLA evaluation of college students in the interactive teaching environment, three methods were used to weight the CLA evaluation indexes, namely, the fuzzy analytic hierarchy process (FAHP), the entropy weight method (EWM), and the coefficient of variation method (CVM). Then a model for evaluating the CLA was constructed, which minimized the CLA improvement difference of college students. Finally, the experimental results verified that the proposed method was effective.